2003
DOI: 10.1002/hup.501
|View full text |Cite
|
Sign up to set email alerts
|

Effect of caffeine on prospective and retrospective duration judgements

Abstract: The effects of caffeine on prospective and retrospective duration judgements were evaluated in a double-blind placebo-controlled experiment. After taking either 200 mg caffeine or a placebo, participants touched a 17-sided polygon for 15 s. Then they verbally estimated the number of angles and the duration. Participants in the prospective group were told in advance they would be making a duration estimate, whereas those in the retrospective group were not told. Caffeine reduced duration estimates in the prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 38 publications
3
20
0
3
Order By: Relevance
“…Men showed no significant effect of caffeine on duration estimates. However, the method that Botella et al used complicates the interpretation of their findings (Gruber and Block, 2003). Gruber and Block (2003) found that 200 mg of caffeine decreased prospective duration judgements when participants performed an active informationprocessing task, but it did not affect judgements in the retrospective paradigm (in which a person is not aware during a duration that time estimation is relevant and important).…”
Section: Caffeine and Time Estimationmentioning
confidence: 96%
“…Men showed no significant effect of caffeine on duration estimates. However, the method that Botella et al used complicates the interpretation of their findings (Gruber and Block, 2003). Gruber and Block (2003) found that 200 mg of caffeine decreased prospective duration judgements when participants performed an active informationprocessing task, but it did not affect judgements in the retrospective paradigm (in which a person is not aware during a duration that time estimation is relevant and important).…”
Section: Caffeine and Time Estimationmentioning
confidence: 96%
“…The discrepancy between Botella et al and the present findings cannot be readily attributed to differences in the sex of the participants, since our sample was also predominantly female. Although caution is needed when considering an outcome that is gender-specific, taskspecific, and dose-specific, the discrepancy between studies might again reflect differences in target interval-10 s in the case of Botella et al It may be noteworthy that Gruber and Block (2003) found effects of caffeine on estimates of a similar time interval, 15 s. Further studies of caffeine's effects on intervals substantially longer than ours would clearly be useful. Gruber and Block (2003) also reported that their effects of caffeine on timing cannot be explained easily by recourse to a single timer, since caffeine only affected performance when estimates were requested prospectively, not when requested retrospectively.…”
Section: Discussionmentioning
confidence: 60%
“…Although caution is needed when considering an outcome that is gender-specific, taskspecific, and dose-specific, the discrepancy between studies might again reflect differences in target interval-10 s in the case of Botella et al It may be noteworthy that Gruber and Block (2003) found effects of caffeine on estimates of a similar time interval, 15 s. Further studies of caffeine's effects on intervals substantially longer than ours would clearly be useful. Gruber and Block (2003) also reported that their effects of caffeine on timing cannot be explained easily by recourse to a single timer, since caffeine only affected performance when estimates were requested prospectively, not when requested retrospectively. Relatedly, in the present series of experiments, the selectivity of caffeine's effects for reaction time performance rather than for time production or discrimination seems inconsistent with the idea that time estimation and reaction time are based on a single (or, at least, common) oscillator (e.g., Treisman et al 1992).…”
Section: Discussionmentioning
confidence: 60%
“…Mesmo sendo este procedimento amplamente utilizado nas investigações sobre percepção de tempo, há muitos anos (Gruber & Block, 2003;Hancock, 1993;Hicks et al, 1976;Miller et al, 1978; Vierordt, 1868 citado por Lejeune & Wearden, 2009), há diversas críticas quanto a sua precisão e validade enquanto método experimental. Desde Watson (1913) a introspecção, entendida como julgamento/classificação verbal que um participante emite sobre estados internos do seu corpo, já era criticada como método experimental impreciso.…”
Section: Conceituações De Tempo E Percepçãounclassified
“…Um importante procedimento no campo de estudo da percepção de tempo é a divisão das situações de pesquisa em prospectivas ou retrospectivas ( Ades, 2002;Block, Hancook & Zakay, 2000;Gruber & Block, 2003;Hicks, 1992;Wearden, 2005;Wearden, 2008;Zakay & Block, 2004). Tal divisão, já era proposta por William James em seu clássico texto de 1890, Em termos práticos a proposição de James é aplicada hoje da seguinte forma.…”
Section: Estimativa Prospectiva E Estimativa Retrospectivaunclassified